Tape nanolithography: a rapid and simple method for fabricating flexible, wearable nanophotonic devices. (December 2018) - Wang, Qiugu; Han, Weikun; Wang, Yifei; Lu, Meng; Dong, Liang
Abstract This paper describes a tape nanolithography method for the rapid and economical manufacturing of flexible, wearable nanophotonic devices. This method involves the soft lithography of a donor substrate with air-void nanopatterns, subsequent deposition of materials onto the substrate surface, followed by direct taping and peeling of the deposited materials by an adhesive tape. Without using any sophisticated techniques, the nanopatterns, which are preformed on the surface of the donor substrate, automatically emerge in the deposited materials. The nanopatterns can then be transferred to the tape surface. By leveraging the works of adhesion at the interfaces of the donor substrate-deposited material-tape assembly, this method not only demonstrates sub-hundred-nanometer resolution in the transferred nanopatterns on an area of multiple square inches but also exhibits high versatility and flexibility for configuring the shapes, dimensions, and material compositions of tape-supported nanopatterns to tune their optical properties. After the tape transfer, the materials that remain at the bottom of the air-void nanopatterns on the donor substrate exhibit shapes complementary to the transferred nanopatterns on the tape surface but maintain the same composition, thus also acting as functional nanophotonic structures. Using tape nanolithography, we demonstrate several tape-supported plasmonic, dielectric, and metallo-dielectric nanostructures, as well as several devices such as refractive index sensors, conformable plasmonic surfaces, and Fabry-Perot cavity resonators. Further, we demonstrate tape nanolithography-assisted manufacturing of a standalone plasmonic nanohole film and its transfer to unconventional substrates such as a cleaved facet and the curved side of an optical fiber. Photonics: Nanolithography for flexible devices Tape nanolithography enables the rapid and low-cost fabrication of a range of photonic devices. The use of tape to facilitate the transfer of patterns from a substrate is known to provide a versatile and simplistic approach for fabricating uniform patterns. Now, a team led by Liang Dong at Iowa State University, USA, deposits metal and dielectric films onto a nanoscale, prepatterned PDMS substrate, and then applies a tape to remove the patterned surface for subsequent transfer. Using this approach various nanopatterned surfaces are demonstrated, including their application in devices such as refractive index sensor, plasmonic surface and Fabry-Perot cavity resonator, all of which are flexible and thus could be used for conformable electronics and photonics.